Treating Cattle to Protect People? Impact of Footbath Insecticide Treatment on Tsetse Density in Chad - Ndeledje, Noël (Public Library of Science, 2013)
BACKGROUND: In Chad, several species of tsetse flies (Genus: Glossina ) transmit African animal trypanosomoses (AAT), which represents a major obstacle to cattle rearing, and sleeping sickness, which impacts public health. After the failure of past interventions to eradicate tsetse, the government of Chad is now looking for other approaches that integrate cost-effective intervention techniques, which can be applied by the stake holders to control tsetse-transmitted trypanosomoses in a sustainable manner. The present study thus attempted to assess the efficacy of restricted application of insecticides to cattle leg extremities using footbaths for controlling Glossina m. submorsitans, G . tachinoides and G . f . fuscipes in southern Chad. METHODOLOGY/PRINCIPAL FINDINGS: Two sites were included, one close to the historical human African trypanosomiasis (HAT) focus of Moundou and the other to the active foci of Bodo and Moissala. At both sites, a treated and an untreated herd were compared. In the treatment sites, cattle were treated on a regular basis using a formulation of deltamethrin 0.005% (67 to 98 cattle were treated in one of the sites and 88 to 102 in the other one). For each herd, tsetse densities were monthly monitored using 7 biconical traps set along the river and beside the cattle pen from February to December 2009. The impact of footbath treatment on tsetse populations was strong (p < 10(-3)) with a reduction of 80% in total tsetse catches by the end of the 6-month footbath treatment. CONCLUSIONS/SIGNIFICANCE: The impact of footbath treatment as a vector control tool within an integrated strategy to manage AAT and HAT is discussed in the framework of the “One Health” concept. Like other techniques based on the treatment of cattle, this technology should be used under controlled conditions, in order to avoid the development of insecticide and acaricide resistance in tsetse and tick populations, respectively.